The development of a questionnaire assessing the outcome of memory rehabilitation for people with acquired brain injury - Chouliara, Niki (2013)
Part A: Memory rehabilitation is a promising approach to address memory difficulties although its effectiveness with neurologically impaired individuals is yet to be established (Chapter 1). This thesis was conducted within the context of the pilot and main phase of a randomised controlled trial (ReMind) evaluating the effectiveness of memory rehabilitation for people experiencing memory problems following traumatic brain injury (TBI), stroke and multiple sclerosis (MS). The trial compared the effects of restitutive and compensatory memory rehabilitation strategies with a self-help control intervention on memory functioning, mood, activities of daily living and mental adjustment. The quantitative data obtained in this trial did not provide strong evidence to support the effectiveness of the intervention. The use of inappropriate outcome measures may account for the contradictory or inconclusive findings of the ReMind and other memory rehabilitation studies. Chapter 2 provides a review of measures that were used in the ReMind trial and/or were commonly used to evaluate outcome in memory rehabilitation studies. A lack of measures that considers the aims of memory rehabilitation and the needs of neurologically impaired individuals was observed. The post-intervention interviews of participants (N=19) in the pilot phase of the ReMind were analysed thematically (Chapter 3). Participants reported benefits in areas that were not covered by existing quantitative outcome measures such as insight into the nature and severity of their memory problems, confidence in their ability to manage these difficulties and qualitative improvements in the use of memory aids.